Management guide for sustainable production of frankincense: a manual for extension workers and companies managing dry forests for resin production and marketing - Lemenih, Mulugeta; Kassa, H. (Center for International Forestry Research, 2011)
This guide is intended for frankincense producers, extension workers and companies engaged in producing frankincense. Gum olibanum (frankincense) from Boswellia papyrifera (Del.) Hochst has been collected and traded for centuries. Although production levels in Ethiopia fall far short of the country’s potential, export volume and earnings from frankincense have been significantly increasing since the late 1990s. But knowledge regarding the biology and ecophysiology of the tree, the frankincense collecting process and post-harvest handling remain largely inadequate. This guide contributes toward filling this gap by providing technical information in three specific areas: how to better manage the species, how to properly tap the tree for increased and sustainable production and how to improve and maintain product quality through improved collection and handling. Section One of the guide introduces dry land areas of Ethiopia. The second and third sections describe the genus, the species and the distribution of Boswellia species. Flowering, seed production and propagation aspects are treated in Section Four while Section Five covers tapping and post-harvest handling of frankincense. Measures for sustainable frankincense production are discussed in Section Six whereas property rights and institutionalisation of responsible management systems are discussed in Section Seven. Finally, Section Eight briefly outlines key issues that require further research. Effective use of information in the guide can help in sustaining supply of frankincense by increasing income of producers and enhancing the responsible management of Boswellia forests in Ethiopia.